2004
DOI: 10.1111/j.1600-079x.2004.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin increases cell proliferation in the dentate gyrus of maternally separated rats

Abstract: Melatonin in mammals, produced by the pineal gland and elsewhere, has shown antioxidant and neuroprotective properties in neuronal cells. We investigated whether melatonin would increase newly born cells (cell proliferation) in the dentate gyrus of maternally separated rats. To examine the effect of melatonin on cell proliferation of the dentate gyrus in maternally separated rats, 5-bromo-2'-deoxyuridine (BrdU) immunohistochemistry was performed. Rat pups were separated from their mothers and socially isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 29 publications
3
44
5
Order By: Relevance
“…These results were in some contrast to another study, in which melatonin reportedly increased cell proliferation in the dentate gyrus of maternally separated young rats and in non-separated rats after 7 days treatment (Kim et al, 2004). Besides the species differences that study also used a cumulative BrdU-labeling protocol, blurring the distinction between proliferation and survival effects.…”
Section: Melatonin Increases Precursor Cell Survivalcontrasting
confidence: 79%
See 1 more Smart Citation
“…These results were in some contrast to another study, in which melatonin reportedly increased cell proliferation in the dentate gyrus of maternally separated young rats and in non-separated rats after 7 days treatment (Kim et al, 2004). Besides the species differences that study also used a cumulative BrdU-labeling protocol, blurring the distinction between proliferation and survival effects.…”
Section: Melatonin Increases Precursor Cell Survivalcontrasting
confidence: 79%
“…Melatonin modulated proliferative activity in the dentate gyrus in early postnatal rats (Kim et al, 2004) and influenced proliferation and differentiation of embryonic neural stem cells (Moriya et al, 2007). In addition, melatonin increased differentiation of rat midbrain neural stem cells (Kong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…More recently it has been reported that exogenous melatonin could increase the survival of neuronal progenitor cells and postmitotic immature neurons in the hippocampus of adult mice (Ramírez-Rodríguez et al, 2009), consistent with melatonin actions on proliferative activity in the rat dentate gyrus and embryonic neural stem cells (Kim et al, 2004;Moriya et al, 2007). These findings are particularly interesting in view of the recent reports that melatonin can reduce learning and memory deficits in mice models of Alzheimer disease (Feng et al, 2004;Olcese et al, 2009).…”
Section: B Melatonin Receptor Functionmentioning
confidence: 58%
“…Recently, exogenous melatonin was reported as effective in preventing hippocampal neuronal death and cognitive dysfunction that follow maternal deprivation in the developing rat, a situation involving increased GC levels, over-expression of GC *Address correspondence to this author at the Departamento de Fisiología, Facultad de Medicina, UBA, Paraguay 2155, 1121 Buenos Aires, Argentina; Tel/Fax: 54-11-59509611; E-mail: dcardinali@fmed.uba.ar receptor genes, and oxidative stress [13]. Indeed, melatonin decreased the expression of GC receptor and increased cell proliferation in the dentate gyrus of maternally deprived neonatal rats [14].…”
Section: Introductionmentioning
confidence: 99%